Triple Bottom Line on Business Performance: Examining the Moderating Role of Managerial Competencies - Asraf, Asraf; Supriaddin, Nofal (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study evaluates the influence of the Triple Bottom Line (TBL) dimensions Economic, Social, and Environmental on restaurant business performance in Kendari, as well as the role of managerial competency moderation. The results show that the three dimensions of TBL have a significant positive influence, with the Economic and Social dimensions directly improving performance, and environmentally friendly policies also play an important role. Managerial competence strengthens TBL's positive impact on business performance. These findings imply the importance of managerial competence in maximizing the benefits of TBL to support business sustainability holistically